Evaluation of the economic crisis on the conservation of the ichthyofauna in Marine Protected Areas. (January 2023) - Arcas, Esther; Valle, Carlos; Forcada, Aitor
Abstract: The use of marine protected areas can be an effective way to simultaneously achieve both conservation and fisheries management objectives. The creation of marine protected areas, in addition to many benefits, also entails several costs, including the need for financing to maintain adequate surveillance and conservation. The recent economic crisis significantly lowered budgets for the maintenance of Spanish Marine Protected Areas, that may have had serious consequences for the marine resources sustainability. In this study we evaluated the indirect impact of the 2008 economic crisis on the conservation of fish stocks in Marine Protected Areas. We compared the number of species, abundance and biomass levels of the ichthyofauna, and abundance and biomass of selected species in two marine reserves (Cabo de San Antonio and Tabarca Island) with control areas, two years before (2008 and 2010) and two years after (2014 and 2015) the budget cut. Results in San Antonio revealed a decrease in total abundance, total biomass and number of species after the crisis, which translates into a decrease in the reserve effect. While in Tabarca no reduction has been observed in these variables, so the reserve effect was maintained after the crisis. We have found that of the 18 species analyzed, in San Antonio the abundance and biomass of 8 and 6 species respectively have decreased after the crisis, while in Tabarca the abundance and biomass of 6 and 8 species respectively have decreased after the crisis. Therefore, surveillance in marine reserves is necessary for the conservation of the species.